A randomized multi‐institutional crossover comparison of the GlideScope® Cobalt Video laryngoscope to the flexible fiberoptic bronchoscope in a Pierre Robin manikin. Issue 8 (27th April 2015) - Fiadjoe, John E.; Hirschfeld, Matthew; Wu, Stephan; Markley, James; Gurnaney, Harshad; Jawad, Abbas F.; Stricker, Paul; Kilbaugh, Todd; Ross, Patrick; Kovatsis, Pete
Summary: Background: The GlideScope Cobalt Video laryngoscope is being used more often in children with challenging laryngoscopy. There are, however, no pediatric trials comparing it to flexible fiberoptic bronchoscopy, the current accepted gold standard. This preliminary manikin study compares the first‐attempt intubation success of the GlideScope Cobalt video laryngoscope to the flexible fiberoptic bronchoscope when performed by attending pediatric anesthesiologists at two major pediatric centers. Methods: This prospective randomized, crossover study evaluated 120 attempts (60 with each study device) to intubate the AirSim Pierre Robin manikin (PRM) with fiberoptic bronchoscopy and video laryngoscopy (VL). Attending pediatric anesthesiologists from two quaternary pediatric centers were eligible to participate. Each attending anesthesiologist randomly performed a single tracheal intubation attempt with one of the study devices followed by the alternate method. The primary outcome was the first‐attempt success rate of tracheal intubation. Blinding was not feasible. We hypothesized that first‐attempt success would be higher with fiberoptic bronchoscopy. Results: Thirty anesthesiologists from each center were randomized to use one of the study devices followed by the alternate method. We analyzed all participants' data. There was no overall difference in first‐attempt success between VL and fiberoptic bronchoscopy (88.3% vs 85% respectively, P = 0.59). There were significant institutional differences in first‐attempt success using VL (76.7% vs 100%). Conclusions: There was no difference in first‐attempt success of tracheal intubation using VL vs fiberoptic bronchoscopy when performed by attending anesthesiologists at two large pediatric centers. However, institutional differences exist in success rates with VL across the two centers. Results from single‐center device evaluations should be verified by multi‐center evaluations. A significant proportion of attending anesthesiologists lack experience with advanced airway devices; targeted education may enhance intubation success and patient safety. Abstract :